In vivo Studies of Protein Binding of Ketorolac in Rat Model by UV-VIS Spectrophotometry and High Performance Liquid Chromatographic Methods - Karim, SM Rezaul; Koly, Sabiha Ferdowsy; Amran, Md Shah; Kabir, Shaila (Dhaka University Journal of Pharmaceutical Sciences, 2016)
In this study, an attempt has been made to determine the protein binding of ketorolac at different time and concentration in rat model. A total of ten rats were used for this study. The rats were subdivided into two groups and 100?g/ml and 200?g/ml of ketorolac were administered through the intra-peritoneal route to rats of group 1 and group 2, respectively. The serum from the rats were collected and analyzed using UV-VIS spectrophotometry and HPLC. In the UV-VIS Spectrophotometric study, the highest percentage of protein binding for ketorolac was found to be 63.067% in group 1 and 74.63% in group 2. In case of HPLC method, the highest protein binding of ketorolac for group 1 and group 2 were 89.72% and 95.07%, respectively. The observed protein binding percentage of ketorolac by HPLC method was slightly higher than that found in UV-VIS Spectrophotometric method. The result obtained in this study showed that the protein binding of ketorolac changes with the time and drug concentration. The percentage of protein binding was higher for higher drug concentration. Dhaka Univ. J. Pharm. Sci. 15(1): 63-67, 2016 (June)